Sexual Well-Being in Old Age: Effectiveness of an Intervention Program to Promote Sexual Well-Being in Older Community-Dwelling Adults - Sofia von Humboldt; Gail Low; Isabel Leal (Social Sciences)
Objectives: While many people strive for a fulfilling sexual life as they age, the inevitable changes that come with aging can present significant challenges concerning their sexual well-being (SWB). This study aims to present a comparative analysis of the scores in the variables of sexual satisfaction, adjustment to aging (AtA), and satisfaction with life (SwL) before and after the implementation of an intervention program to promote SWB among older adults. Methods: A convenience sample of 117 older community-dwelling adults (M = 72.31; SD = 5.752) were included in this study, and an ex post facto longitudinal design was applied. A six-week intervention program aimed at improving older adults’ understanding and exchanging their experiences of SWB was performed. The following measures were utilized: (1) a sociodemographic, health and lifestyle questionnaire; (2) Adjustment to Aging Scale (AtAS); (3) Satisfaction with Life Scale (SwLS); (4) New Sexual Satisfaction Scale (NSSS-S); and (5) Mini-Mental Status Exam (MMSE). The specified assessment time points in this study were as follows: baseline and after intervention. A follow-up assessment was conducted 6 months and 12 months after the baseline measurement. Results: The results indicated an increase in the scores in sexual satisfaction, AtA, and SwL from before to after the intervention among the intervention group. Conclusions: The development of intervention programs in older communities is necessary to contribute to the enhancing older adults’ SWB and to explore the best practices for implementing tailored interventions within community settings.